2012
DOI: 10.1007/s00705-012-1395-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome dynamics in three different geographical isolates of white spot syndrome virus (WSSV)

Abstract: White spot syndrome virus (WSSV), the sole member of the monotypic family Nimaviridae, is considered an extremely lethal shrimp pathogen. Despite its impact, some essential biological characteristics related to WSSV genome dynamics, such as the synonymous codon usage pattern and selection pressure in genes, remain to be elucidated. The results show that compositional limitations and mutational pressure determine the codon usage bias and base composition in WSSV. Furthermore, different forces of selective press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Microarrays constructed based on 184 putative ORFs of WSSV-TH confirmed expression of 79% of these ORFs in the gills of P. monodon infected with WSSV [ 54 ]. An analysis of the codons of ORFs (>100 codons) in WSSV-TW, WSSV-CN, and WSSV-TH indicated that codon usage bias and base composition are determined by compositional limitations and mutational pressure [ 55 ]. Interesting features of WSSV ORFs include one exceptionally long ORF—the longest among all viruses, specifically wssv_03600—which is 18,221 bp in the Korean isolate.…”
Section: The Wssv Genome and Mirnasmentioning
confidence: 99%
“…Microarrays constructed based on 184 putative ORFs of WSSV-TH confirmed expression of 79% of these ORFs in the gills of P. monodon infected with WSSV [ 54 ]. An analysis of the codons of ORFs (>100 codons) in WSSV-TW, WSSV-CN, and WSSV-TH indicated that codon usage bias and base composition are determined by compositional limitations and mutational pressure [ 55 ]. Interesting features of WSSV ORFs include one exceptionally long ORF—the longest among all viruses, specifically wssv_03600—which is 18,221 bp in the Korean isolate.…”
Section: The Wssv Genome and Mirnasmentioning
confidence: 99%
“…Several works have addressed the epidemiology and contemporary evolutionary trends of WSSV (14)(15)(16); however, we know little about the ancient history of WSSV, because we have few nimavirus genomes available for comparative analyses. Interestingly, some decapod crustaceans have been shown to harbor fossilized nimaviruses in their genomes (17)(18)(19).…”
mentioning
confidence: 99%
“…However, its sustainability has been at risk in the last decade due to the low production yields triggered by viral outbreaks ( 1 ). Presently, white spot syndrome virus (WSSV) is the most devastating shrimp viral pathogen worldwide, causing mortality of up to 100% of farm production within 2 to 10 days ( 2 ). Classified under a new genus, Whispovirus , in the family Nimaviridae ( 3 ), WSSV is extremely virulent and has a wide host tissue tropism ( 4 ).…”
Section: Genome Announcementmentioning
confidence: 99%